Harmonizing screening methodologies of index institutions for Shariah compliant stocks - Siti Nur Zahirah Omar, Azizi Abu Bakar, Razli Ramli, (Opción)
The purpose of this study is to uncover an acceptable screening method used by the index institutions to reduce the gaps of Shariah-compliant status of a stock. The initial concepts are based on academic literature and followed by interview sessions of nine key experts recognized in the field of Shariah-compliant stocks as respondents. The results of this study have yielded some notable findings. Fund managers who are aware that the investors who appoint them are very much in favour of Shariah-compliant securities will certainly use methods that suit their investors’ appetite. In fact, Shariah advisers have also concurred that the differences between the global index institution’s screening methods are not significant and the differences found are not related to Shariah requirements. Studies on the methodology of such Shariah-compliant stocks screenings are important and have a great impact in ensuring the continued viability of Islamic financial developments so that they are not frustrated by the issue of non-uniformity of Shariah-compliant stock screening methods. In Malaysia, the stock screening method is performed by the Shariah Advisory Council of the Securities Commission of Malaysia (SACSC), while in the global market there are several index institutions such as the Dow Jones Islamic Indexes (DJII), FTSE Shariah Global Equity Index Series (FTSE) and MSCI Islamic Index Series (MSCI), which also have their own Shariah-compliant stock screening method.